Reflections
Reflections: The Story of the Exhibitions, The Treasure Houses of Britain focuses on the behind- the scences story of the creation and installation of one of the most ambitous and seccessful exhibitions the National Gallery of Art has undertaken. With J. Carter Brown as guide, the program takes the viewer through the exhibitionsïs 17 rooms while highting key themes and exploring the showïs history, planning, and desing. Commentary installation footage, provide rare insight into the making of an exhibition